(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article examines the main methods for assessing the effectiveness of public-private partnership (PPP) projects, which play a crucial role in developing infrastructure and providing social services. The study identifies key financial, economic, social, and environmental evaluation tools, including NPV, IRR, Payback Period, and Benefit-Cost Ratio (BCR). The author also highlights the importance of risk analysis and scenario modeling in ensuring the sustainability and feasibility of PPP initiatives. Using international and regional examples (Kazakhstan, Great Britain, Uzbekistan), the article demonstrates the practical significance of comprehensive effectiveness assessment for achieving successful and sustainable PPP outcomes.